Theoretical Analysis of the Framework Lifelong Education on Quality of Life - Winia Waziana; Widi Andewi; Trisnawati Trisnawati; Ponidi Ponidi (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2020)
The people were created by God with a high desire for intellectual curiosity. Therefore humans must be able to learn anywhere and anytime, either in the home, residential environment or educational institutions. This article was to analyse the strategies in lifelong education. It also analyses about the importance of education and open their minds that education is not always obtained from the learning at school. This research was a qualitative study with content analysis as data collection techniques. Lifelong education was a system of educational concepts that includes all activities and learning processes that take place throughout the whole of human life. The direction of lifelong education was in children to adults in order to increase their knowledge and skills that are needed to survive and have a better quality of life. Keywords: Framework Lifelong Education, Quality of life